2005
DOI: 10.1182/blood-2004-06-2272
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and fibrin(ogen) increase metastatic potential by impeding natural killer cell–mediated elimination of tumor cells

Abstract: To test the hypothesis that platelet activation contributes to tumor dissemination, we studied metastasis in mice lacking G␣q, a G protein critical for platelet activation. Loss of platelet activation resulted in a profound diminution in both experimental and spontaneous metastases. IntroductionA persuasive body of evidence has accumulated associating hemostatic factors with tumor growth, stroma formation, and tumor dissemination. [1][2][3] Clinical studies have shown that expression of procoagulants by cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
726
3
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 876 publications
(770 citation statements)
references
References 29 publications
33
726
3
8
Order By: Relevance
“…2b). Several studies showed that an impaired platelet aggregation or a reduced platelet number results in the reduction of metastasis [35]. Our data suggest a direct role of platelets in metastasis in the MT3 model, because the into the surrounding tissue [36].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…2b). Several studies showed that an impaired platelet aggregation or a reduced platelet number results in the reduction of metastasis [35]. Our data suggest a direct role of platelets in metastasis in the MT3 model, because the into the surrounding tissue [36].…”
Section: Discussionsupporting
confidence: 54%
“…It was shown before that the fibrin clots protect the tumor cells from natural killer cell attack [35]. So, the prevention of fibrin clot formation by the D/O-L might enable an easier access of immune cells to the tumor cells facilitating their elimination from the blood stream [35] that resulted in a reduced metastases formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that platelet-fibrin(ogen) clots surrounding tumor cells protect them from immunological and physiological stresses in the bloodstream, and facilitate their lodging to the pulmonary vasculature (Nieswandt et al, 1999). This hypothesis is corroborated by in vivo data, which disclose that in mice lacking functional natural killer (NK) cells, fibrin(ogen) deficiency was no longer a significant determinant of metastatic potential (Palumbo et al, 2005).…”
Section: Introductionmentioning
confidence: 76%
“…Bár a metasztatikus tumorsejtek és a thrombocyták közös aggregátumképzése a keringés-ben több mint 150 éve ismert, a jelenség pontos molekuláris háttere máig tisztázatlan. Számos genetikai és modell állatokkal végzett vizsgálat alapján a keringésbe lépő tumorsejtek sejtfelszínén specifikus, a thrombocyták tumorsejthez való kapcsolódását segítő, azaz thrombocytaaggregációt indukáló fehérjék jelennek meg [2][3][4][5][6][7]. E mechanizmus hiányában a tumorsejtek kevesebb mint 1%-a élné csak túl a keringésben történő vándorlást [8,9].…”
unclassified